Rancang Bangun Aplikasi Penilaian Kinerja Karyawan Berdasarkan Kompetensi Pada PT. Tunggal Djaja Indah - Dewantara, Billy; Sulistiowati, Sulistiowati; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT Tunggal Djaja Indah estabilished in 1963. PT Tunggal Djaja Indah (PT.TDI) the paint factory is a leading paint manufacturer in Indonesia with many experiences in the field of industrial paints. ISO 9001 which has obtained is a proof of seriousness company. Human resource is one of the source of competitive advantage and the key element that are important to achieve a success in competing to achieve the goal. An individual employee performance improvement will encourage the overall human resource that can increase the productivity. Performance assessment is a right answer to the description above. Based on observations and interviews, the company discovered a problem in the process of assessment items were assessed to be in general and not detailed, although the company has structured competency standarts, and the frequent occurrence of errors in the records and the calculation of the assessment data is still done manually as well as the length of time required for run multiple processes in performance assessment. To overcome these problem it will be made an application solution Employee Performance Assessment Based on Competence for PT.TDI. This Application can shorten the process and the time it takes from 26 days to 9 days in the employee performance assessment phase by way of doing automation with competency data recording (1 day), valuation (6 days), valuation analysis (4 days), assessment approval (1 day), reporting the result of the performance assessment (1day).